- #1

rsq_a

- 107

- 1

This is a bit of a shot in the dark, but has anybody ever encountered a theory which can tell me what the solution of this equation:

[tex]A_n = nA_{n-2} + nA_{n-3}[/tex]

behaves like, as [tex]n\to\infty[/tex]? For convenience, you can set [tex]A_n = 1[/tex] for [tex]n = 0, \ldots, 3[/tex]. Without the term on the right, it goes something like [tex]A_n \sim \Gamma(n/2)[/tex].

[tex]A_n = nA_{n-2} + nA_{n-3}[/tex]

behaves like, as [tex]n\to\infty[/tex]? For convenience, you can set [tex]A_n = 1[/tex] for [tex]n = 0, \ldots, 3[/tex]. Without the term on the right, it goes something like [tex]A_n \sim \Gamma(n/2)[/tex].

Last edited: